Local Government Policy in Combating Extreme Poverty: A Systematic Literature Review - Marzuki, M. Ervan (Jurnal Studi Ilmu Pemerintahan, 2024)
This study aims to review research related to local government policies in combating extreme poverty through a systematic literature review, evaluate the effectiveness of these policies in improving living conditions and identify factors that influence their success. This study utilizes the Scopus database and employs RStudio for data visualization to enhance the thoroughness of the literature analysis. The results of this study show the importance of local government policies in combating extreme poverty, emphasizing the need for a tailored approach. In addition, the study also emphasizes the shift from poverty alleviation to development inclusion, decentralization of power, climate change, and food security. Key issues include governance, gender inequality, rural areas, and health inequality. The results of this study provide guidance for policymakers in designing effective intervention programs. However, the study has limitations, including not covering all relevant policies and excluding inputs from stakeholders at the local level. Future research should explore the dynamics of city policies, local community perspectives, and long-term impacts.